2017
DOI: 10.1111/jir.12361
|View full text |Cite
|
Sign up to set email alerts
|

Development and psychometric properties of the Psychological Therapies Outcome Scale – Intellectual Disabilities (PTOS‐ID)

Abstract: This preliminary study suggests that the PTOS-ID is a psychometrically robust measure of psychological distress and psychological well-being that can be used with people with ID. Further research is required to assess its reliability and ability to detect change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…The majority of the identified subjective measures were only found in single studies ( N = 25). The most frequently used subjective measures were as follows (psychometric properties presented in parentheses): Glasgow Anxiety Scale–Intellectual Disability (GAS‐ID; Mindham & Espie, ): internal consistency = 0.93; test‐rest‐reliability = 0.93; concurrent validity = 0.75 Psychological Therapy Outcome Scale–Intellectual Disabilities (PTOS‐ID; Vlissides, Beail, Jackson, Williams, & Golding, ): internal consistency = 0.76–0.81; concurrent validity = 0.85 Health of the Nation Outcome Scales for People with Learning Disabilities (HONOS‐LD; Roy, Matthews, Clifford, Fowler, & Martin, ): internal consistency = 0.96; concurrent validity = 0.66–0.76 Cognitive and Affective Mindfulness Scale‐Revised (CAMS‐R; Feldman, Hayes, Kumar, Greeson, & Laurenceau, ): internal consistency = 0.76; concurrent validity = 0.66. …”
Section: Resultsmentioning
confidence: 99%
“…The majority of the identified subjective measures were only found in single studies ( N = 25). The most frequently used subjective measures were as follows (psychometric properties presented in parentheses): Glasgow Anxiety Scale–Intellectual Disability (GAS‐ID; Mindham & Espie, ): internal consistency = 0.93; test‐rest‐reliability = 0.93; concurrent validity = 0.75 Psychological Therapy Outcome Scale–Intellectual Disabilities (PTOS‐ID; Vlissides, Beail, Jackson, Williams, & Golding, ): internal consistency = 0.76–0.81; concurrent validity = 0.85 Health of the Nation Outcome Scales for People with Learning Disabilities (HONOS‐LD; Roy, Matthews, Clifford, Fowler, & Martin, ): internal consistency = 0.96; concurrent validity = 0.66–0.76 Cognitive and Affective Mindfulness Scale‐Revised (CAMS‐R; Feldman, Hayes, Kumar, Greeson, & Laurenceau, ): internal consistency = 0.76; concurrent validity = 0.66. …”
Section: Resultsmentioning
confidence: 99%
“…As highlighted by Vlissides et al . (), the measurement of construct validity corresponding to general clinical measures utilised with ID populations has been severely lacking to date and is therefore examined here for the CORE‐LD30. A principal components analysis with oblique rotation resulted in the final extraction of three separate domains and an indication that the overall measure does indeed function appropriately as a ‘core’ measure.…”
Section: Discussionmentioning
confidence: 99%
“…Vlissides et al . () found many of the single and multi‐trait measures available for use with people with ID had some good psychometric properties but construct validity assessment was lacking, with the only trans‐diagnostic measure with construct validity evaluation using factor analysis was the Brief Symptom Inventory (BSI) (Derogatis ), which has not been developed as a specific measure for this population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical trials in intellectual disabilities are often complex and difficult to conduct, and the results may be affected by the relative scarcity of valid and reliable outcome measures. We are keen to support the publication of articles reporting on the development and validation of reliable outcome measures for trials and practice, such as the psychological therapies outcome scale -ID (PTOS-ID) reported in this issue (Vlissides et al 2017). The authors recommend further work to establish its reliability and ability to measure change.…”
mentioning
confidence: 98%